Trends and predictions of the global burden of ischemic heart disease in women of childbearing age attribute to high body mass index and hypertension,1990–2021: a systematic analysis for the Global Burden of Disease Study - Qi Gu; Shuxiong Nong; Chenang Liu; Yongfeng Chen; Meng Wu; Chilin Liao; Cong Hu (BMC Cardiovascular Disorders)
Abstract Background High body mass index (BMI) and hypertension are quite prevalent in women of childbearing age (WCBA) and are also common risk factors for ischemic heart disease (IHD). However, there are few studies globally evaluating the burden of IHD of WCBA attribute to high BMI and hypertension. Methods The DALYs (Disability-adjusted life years), Deaths, YLDs (Year lived with disabilitys), YLLs (Year of life losts) of IHD in WCBA attributable to high BMI and hypertension were analyzed by age, sex, year, and geographical location and Socio-demographic Index (SDI). To assess the contribution of epidemiological changes, population growth, and population ageing, a decomposition analysis was used. Exponential Smoothing (ES) modeling and the Autoregressive Integrated Moving Average (ARIMA) model were used to predict the global ASDR (age-standardized DALYs rate), ASMR (age-standardized mortality rate) attributed to the 2 risk factors from 2022 to 2050. The cluster analysis was used to evaluate the changing pattern of burden across GBD regions. Results In 2021, the number of global deaths attribution to high BMI was 9,865,138 (95% UI: 3,845,800–15,976,196), and the corresponding ASMR was 216.05 (95% UI: 84.26–349.49) per 100000 population. In various age groups, the largest increase occurred in 20–24 years group (EAPC = 1.26 (95% CI:1.13–1.39)). The number of DALYs of IHD in WCBA attribution to hypertension is 2,158,633 (95% UI:1,725,994–2,538,752) with a corresponding ASMR 46.05 (95% UI: 36.87–54.15) per 100,000 population. The number of DALYs of IHD in WCBA attribution to hypertension is 37,920,567 (95% UI: 30,389,745–44,641,339), and the corresponding ASDR is 817.79 (95% UI: 655.74–962.67) per 100000 population. The largest number of Deaths and DALYs of IHD in WCBA was found between 45–49 years. From 1990 to 2021, ASMR and ASDR attributable to high BMI and hypertension led to a sustained upward trend in Low and Low-medium SDI regions. In addition, the ASMR and ASDR for high BMI and hypertension are highest in the Low-middle SDI regions. Globally, from 1990 to 2021, the overall changes in ASMR and ASDR indicate a relatively stable trend in IHD in WCNA attribute to high BMI. Meanwhile, ASMR and ASDR showed an overall downward trend for hypertension. The number of DALYs, deaths, YLLs, and YLDs of IHD in WCBA attribution to high BMI and hypertension based on the ES and ASMIR models are all increasing from 2022 to 2050. Conclusions Over the past 30 years, the ASMR and ASDR of IHD in WCBA has continued to rise. Countries need to remain vigilant about the increasing burden of IHD in WCBA attribute to high BMI and hypertension. It requires proactive prevention strategies, strict control of risk factors, and increased medical coverage to alleviate the burden of IHD. Each region should develop more proactive and effective strategic measures.